Application of a new system for classifying root canal morphology in undergraduate teaching and clinical practice: a national survey in Malaysia - Ahmed, Hany Mohamed Aly; Che Ab. Aziz, Zeti Adura; Azami, Noor Hayati; Farook, Mohideen Salihu; Khan, Asfand Ali; Mohd Noor, N.S.; Ayoub, A.A.; Zainal Abidin, Imran; Halim, Mohamad Syahrizal; Pai, A. R.V.; Kacharaju, Kranthi Raja; Mohammad, Norazlina; et al. (Blackwell Publishing Ltd, 2020)
Aim To evaluate and compare the feedback of final year undergraduate dental students in eight Malaysian dental schools on the application of a new system for classifying root canal morphology in teaching and clinical practice.